معالجة العنف من منظور سوسيولوجي - هيثم, علي; سرمد, محمد (جامعة الوادي - University of Eloued, 2017)
تعد دراسة السلوك العنيف عامة والعنف الأسري ضد المرأة خاصة من الموضوعات التي أهتم بها الكثير من الباحثين والعلماء في فروع العلم المختلفة، ويعد علم الاجتماع احد هذه العلوم التي اهتمت بالسلوك الانحرافي اهتماما بالغاً. فالمجتمعات الإنسانية المختلفة مع تقدمها وتطورها وتعدد أنماط العلاقات الاجتماعية وتشابكها وتعقيدها ظهرت فيها تناقضات اجتماعية وصراعات فردية أعلنت عن وجودها في مظاهر متباينة وسلوك انحرافي ناجم عن تلك الصراعات التي تؤدي إلى الأضرار بالنظام الاجتماعي. ويقرر الكثير من الباحثين ان التحولات الاجتماعية والاقتصادية تصاحبها ظهور أشكال متعددة من السلوك الانحرافي في المجتمع. والمجتمعات تمر بمراحل معينة من التغير قد يظهر معها بعض الفجوات والمتغيرات الناجمة عن التمسك بالقديم واخذ ينسحب على الدول النامية. ونحاول في هذا البحث التعرف على العنف وأنواعه وأسبابه ومن ثم وضع الحلول المناسبة له. Abstract : The treatment of violence according to sociological prospective Studying of violent behavior especially against woman is one of most important subjects in which the scientists and researchers focus on , sociology also focuses on this field, it studies the deflected behavior because have developed in their valuation and patterns, this development will make asocial complication and contradiction. at the and these complication and contradiction will make a conflict between individuals , so this will create a damage in the social system many of sociologists insist that the economic and social changes will create many shapes of deflected behavior with in society. Societies have than formed from phase to another, this transforming creates hollows in the coherence of society , also this social changing appears in the countries of the third world. This research presents introduction about violence and its types, reasons and treatments.
مقال
Keywords: السلوك الانحرافي، العنف، المعالجة السوسيولوجية; first concept, second concept, the third concept